2020
DOI: 10.1002/ecs2.3066
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances drive changes in coral community assemblages and coral calcification capacity

Abstract: Anthropogenic environmental change has increased coral reef disturbance regimes in recent decades, altering the structure and function of many coral reefs globally. In this study, we used coral community survey data collected from 1996 to 2015 to evaluate reef-scale coral calcification capacity (CCC) dynamics with respect to recorded pulse disturbances for 121 reef sites in the Main Hawaiian Islands and Mo'orea (French Polynesia) in the Pacific and the Florida Keys Reef Tract and St. John (U.S. Virgin Islands)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 81 publications
3
37
0
Order By: Relevance
“…Furthermore, we found greater changes over time in coral assemblages compared to those of trait assemblages due to the widespread dominance of non‐framework species and the stasis of reef framework corals in the region, which suggests that reef functions were already limited at the onset of our study. Our findings correspond to those obtained by other studies that have found that opportunistic coral species are increasingly dominating Caribbean reefs with no evidence of the functional recuperation of main reef‐builders (e.g., Alvarez‐Filip et al., 2013; Courtney et al., 2020; Green et al., 2008; McWilliam et al., 2020; Perry et al., 2015; Toth et al., 2019), suggesting that the decoupling between coral recovery and functional recovery that we report here might also be likely to occur in other reef areas in the Caribbean.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found greater changes over time in coral assemblages compared to those of trait assemblages due to the widespread dominance of non‐framework species and the stasis of reef framework corals in the region, which suggests that reef functions were already limited at the onset of our study. Our findings correspond to those obtained by other studies that have found that opportunistic coral species are increasingly dominating Caribbean reefs with no evidence of the functional recuperation of main reef‐builders (e.g., Alvarez‐Filip et al., 2013; Courtney et al., 2020; Green et al., 2008; McWilliam et al., 2020; Perry et al., 2015; Toth et al., 2019), suggesting that the decoupling between coral recovery and functional recovery that we report here might also be likely to occur in other reef areas in the Caribbean.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, future ecosystem functionality depends on which species successfully recover (Alvarez‐Filip et al., 2013; Cabral‐Tena et al., 2018; Perry & Alvarez‐Filip, 2019). Therefore, assessments of the trajectories that determine the physical functionality of reefs after a disturbance are particularly relevant given that there is little evidence that reefs recover to their initial functional states (Courtney et al., 2020; McWilliam et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems throughout the world are increasingly threatened by multiple natural and anthropogenic stressors, often leading to ecosystem shifts from desirable to less desirable states [ 1 4 ]. Coral reefs are the some of the most diverse ecosystems on Earth, and the transition between disturbance states is often observed through changes in coral reef community composition and ecosystem function [ 5 7 ]. The desired state is an environment that supports critical ecological processes and resulting patterns across space and time, such as overall system production, key predator-prey (or grazer) interactions, and reproduction across multiple functional groups [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shifting community structure can also alter metabolic estimates 10,31 . In times of stress, fast-growing, habitatforming coral groups are replaced with weedy coral and algal species 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Changing rates of G net and P net can indicate growth 9 , degradation [16][17][18] or phase shifting 16,19,20 . Higher rates of G net tend to indicate reefs with higher coral cover 9,21,22 , and ecosystems which have not been impacted by significant stressors [23][24][25][26] , whereas declining and net-dissolving calcification rates indicate stressed corals 16,18,27 or ecosystems which have little to no live corals 25,28 . Therefore, G net and P net are increasingly used as proxies for coral reef ecosystem health 10,29,30 .…”
mentioning
confidence: 99%